Deconfinement transition line with the complex Langevin equation up to μ/T∼5 - Scherzer, Manuel; Sexty, Dénes; Stamatescu, Ion-Olimpiu (Physical review, 2020)
We study the deconfinement transition line in QCD for quark chemical potentials up to μq∼5 T (μB∼15 T). To circumvent the sign problem we use the complex Langevin equation with gauge cooling. The plaquette gauge action is used with two flavors of naive Wilson fermions at a relatively heavy pion mass of roughly 1.3 GeV. A quadratic dependence describes the transition line well on the whole chemical potential range.
Gesehen am 16.10.2020